Quintech Industries Sdn Bhd / Mohd Salleh Yusof ... [et al.] - Yusof, Mohd Salleh; Hasim, Hazirah; Halidi, Norhaniza; Saidin, Norhasfalina; Mansor, Ahmad Hasnan (2004)
Quintech Industries Sdn Bhd is one of the new companies that produce a water tank and septic tank form fiberglass for housing purpose. This kind of business is quite new and it is an advantage for us because we don’t have many competitors and we can enter the market easily. Our business location is in Sg. Petani, Kedah.